2021
DOI: 10.1016/j.jor.2021.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal steroid injections during the COVID-19 pandemic

Abstract: Introduction This study aims to determine whether musculoskeletal corticosteroid injections increase the risk for COVID-19. Method 734 patients who received a corticosteroid injection during the COVID-19 pandemic were followed and their COVID status within 30 days after the injection checked. The results were then compared with an age and sex matched control group. Results No statistically significant difference in the frequency of COVID-19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…A prior prospective study by our group showed no evidence of an increased risk of COVID-19 during the lockdown period of the current pandemic ( 23 ). Additional retrospective studies with cohorts ranging from 30 to 734 participants have shown similar results since then ( 19 , 24 26 ). The findings during the recovery period in our state further support the safety of intra-articular and spine corticosteroid injections during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A prior prospective study by our group showed no evidence of an increased risk of COVID-19 during the lockdown period of the current pandemic ( 23 ). Additional retrospective studies with cohorts ranging from 30 to 734 participants have shown similar results since then ( 19 , 24 26 ). The findings during the recovery period in our state further support the safety of intra-articular and spine corticosteroid injections during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 55%
“…The results of studies evaluating individuals who received injections during the lockdown period have been reassuring, but the changes in public health policies, including decreased physical distancing and the reopening of businesses, and potentially higher exposure when vaccines were not yet available, warrant additional investigation about the safety profile of corticosteroid injections during the COVID-19 pandemic ( 19 , 23 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, COVID-19 infection precipitously progresses, and respiratory failure can occur [ 3 ]. Therefore, prognostic factors for COVID-19 progression were investigated to provide a basis on which to optimize hospital efforts, further improve patient management and make therapy more effective, hoping to reduce mortality [ 4 , 5 ]. Gender, age, underlying comorbidities (diabetes, hypertension, cardiovascular disease), respiratory rate, temperature, neutrophil and lymphocyte counts, D-dimer, albumin and procalcitonin are all predictors of COVID-19 severity, and therefore can be considered risk factors for admission to intensive care unit (ICU) [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, COVID-19 infection precipitously progresses, and respiratory failure can occur [3]. Therefore, prognostic factors for COVID-19 progression were investigated to provide a basis on which to optimize hospital efforts, further improve patient management and make therapy more effective, hoping to reduce mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, and specifically related to the COVID-19 pandemic where elective surgeries are postponed, preoperative ICIs are effective in improving patient quality-of-life during the delay to surgery. Reassuringly, studies of patients given ICI during the COVID-19 pandemic in the UK did not show any increase in COVID-19 infection or adverse effects [ 77 , 78 ]; therefore, ICI may be a safe and viable option. Of note, while ICI clinics may also work at reduced capacities during the pandemic, reinstating ICI clinics could be a practical and more feasible approach to combat the significant delays in elective surgeries.…”
Section: Introductionmentioning
confidence: 99%